Generating dynamic social networks from large scale unstructured data - Estes, Tim.; Safari eBooks; O'Reilly strata making data work conference (2011 : Santa, Calif.) ([United States?] : O'Reilly Media, 2011)
"Developing a social network map is fundamental to comprehensively understanding a person. Social networks are dynamic and better derived from real-world data than static configurations. However, the vast majority of this real world data is unstructured. This presentation will show how Synthesys uses very large scale unstructured data to create social network maps for reporting and further analysis." --Resource description page.
Title from title screen.
Recorded at O'Reilly strata making data work conference: Feb. 1-3, 2011, Santa Clara, Calif.
Electronic reproduction.
Keywords: Data mining; Online social networks; Electronic books